“However Long the Night, the Dawn Will Break”: Rebuilding a Shattered Art World in the New Liberia. - Chandler, RobinM. (Journal of Arts Management, Law & Society, 2013)
The article presents author's comments on the transformational change and transnational cooperation in the African community that materialized social movement, post-colonial politics, and liberation struggles. It mentions that the members of the Liberian arts community is focused on the creation of the National Arts Council by the Government of Liberia and Liberia President, Ellen Johnson Sirleaf.